Musashi - Yoshikawa, Eiji, 1892-1962.; Terry, Charles S. (Tokyo : Kodansha International, 1981)
Musashi Miyamoto fights in 1600 for the losing side of the battle at Sekigahara when the Tokugawa Shogunate begins its reign.
This epic recounts the life and times of medieval Japan's greatest swordsman--a man who began life as an over-eager lout but turned himself into a master of his chosen weapon. But his life was spent not only in training to perfect the art of killing, but also in a quest to conquer himself. Unable to settle down, Musashi embarks on the life of a ronin (masterless samurai) as he wends his way through the feudal world of medieval Japan in his search for perfection. In the process he finds a young woman who loves him and many enemies who seek his destruction, including the most feared swordsman of all. The book teems with memorable characters, many of them historical. Interweaving themes of unrequited love, misguided revenge, filial piety and dedication to the Way of the Samurai, it depicts vividly a world Westerners know only vaguely.
Translation of : Miyamoto Musashi.
Keywords: Miyamoto, Musashi, -- 1584-1645 -- Fiction; Swordsmen -- Japan -- Fiction; Japan -- History -- 17th century -- Fiction; Historical fiction; Biographical fiction